(untitled) (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Pectin has several unique properties that enabled it to be use as a matrix for entrapment and/or delivery of a variety of drugs, proteins and cells. They are used in pharmaceutical as carriers in drug delivery, and in the treatment of various disease conditions. Objectives: This study aimed at determining percentage yield of pectin, extracted from unripe, ripe, and overripe Banana (Musa acuminata L. Musaceae) and Plantain (Musa paradisiaca L. Musaceae) peels and to evaluate their antioxidant activities. Materials and Method: Pectins were extracted from the stated samples using conventional extraction method involving alcohol precipitation, and the percentage yields were calculated. The DPPH antiradical activity and reducing capacity was assayed, using Ascorbic acid as standard. Results: The percentage yield of pectin were obtained as 3.04±0.97%, 5.84±0.49%, 3.70±0.68% for banana and 4.65±0.70%, 6.61±0.21%, 6.91±0.86% for plantain corresponding to unripe, ripe, and overripe respectively. The extracted pectin of all the samples were observed to be statistically inferior to when compared to the standard used Ascorbic acid at all concentrations of samples prepared for both DPPH antiradical activity assay and Reducing capacity assay (p ≤ 0.005), at 95% confidence interval. Conclusion: The yield of banana peel pectin have an initial increase with ripening followed by a decrease in yield, while plantain peel pectin can be said to increase from its unripe stage through to its overripe stage; with plantain pectin yield greater than banana across all stages. All data showed statistical inferiority to Ascorbic acid in reducing capacity and against DPPH.